1986
DOI: 10.1128/mcb.6.6.1974
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of two rabbit mammary epithelial cell lines with distinct oncogenic potential and differentiated phenotype after microinjection of transforming genes.

Abstract: The goal of this work was to establish an assay for transformation of epithelial cells. Two epithelial cell lines were obtained after microinjecting transforming genes into primary rabbit mammary secretory cells. The cell lines were analyzed for their oncogenic potential and for the maintenance of a differentiated phenotype. A fully transformed cell line, which retained epithelial cell organization, was obtained by coinjecting simian virus 40 DNA and the activated human c-Ha-ras gene. The proliferation rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…Nevertheless, the effects of SV40 transformation in, for example, rodent hepatocytes (Isom et al, 1980(Isom et al, , 1981 and mammary epithelia (Garcia et al, 1986), and in human keratinocytes (Chang, 1986) have been broadly similar to our observations, i.e. acquisition of anchorage independence (with or without tumorigenicity) but retention of differentiated characteristics.…”
Section: Discussionsupporting
confidence: 68%
“…Nevertheless, the effects of SV40 transformation in, for example, rodent hepatocytes (Isom et al, 1980(Isom et al, , 1981 and mammary epithelia (Garcia et al, 1986), and in human keratinocytes (Chang, 1986) have been broadly similar to our observations, i.e. acquisition of anchorage independence (with or without tumorigenicity) but retention of differentiated characteristics.…”
Section: Discussionsupporting
confidence: 68%
“…Under these conditions the transformants tended to form multilayers ranging from small clusters of cells in 17,2 to five layers of cells in R5. It has been reported that transformed mammary epithelial cells form bilayers when grown on collagen (Garcia et al, 1986). Why these differences in substratum have such an effect on the organization of transformed epithelial cells is not apparent.…”
Section: Morphology Of Transformed Mdck Cellsmentioning
confidence: 97%
“…On the other hand, transformed cells that maintained epithelial characteristics and a high surface membrane uvomorulin content were noninvasive (59). Reductions in cell-cell contacts had been previously reported when pp60 v-src was expressed in MDCK cells (60), and when SV-40-DNA and ras-DNA were used to transform primary rabbit mammary epithelial cells (61).…”
Section: Altered Epithelial Cell Polarity In Pathologic Statesmentioning
confidence: 99%